The 'Megasecoptera–Diaphanopterodea' twilight zone epitomized by a new insect from Xiaheyan (Early Pennsylvanian; China). Issue 2 (2nd April 2020) - Yang, Nan; Ren, Dong; Béthoux, Olivier
Abstract: A new species of 'Megasecoptera-like' insect, Sinodiapha ramosa gen. and sp. nov., is described based on two specimens from the Xiaheyan locality (early Pennsylvanian) of China, one of which displays a wing pair in the neopterous resting position. This unusual combination of venational features and neoptery indicates that the species belongs to the Diaphanopterodea, and that this order derived from the Megasecoptera. We establish the family Sinodiaphidae fam. nov. for the new genus, and the taxon Megasecopteromorpha for the two orders, the latter being most likely paraphyletic. The Diaphanopterodea are highly derived insects and therefore are of no particular relevance to elucidate the ancestral conditions of Pterygota. Nan Yang [yangnan0504@qq.com ], Key Laboratory of Insect Evolution and Environmental Changes, Capital Normal University, Beijing 100048, PR China; Dong Ren [rendong@mail.cnu.edu.cn ], College of Life Sciences, Capital Normal University, 105 Xisanhuanbeilu, Haidian District, Beijing 100048, PR China, and Academy for Multidisciplinary Studies, Capital Normal University, 105 Xisanhuanbeilu, Haidian District, Beijing 100048, PR China; Olivier Béthoux [obethoux@mnhn.fr ], CR2P (Centre de Recherche en Paléontologie — Paris), MNHN – CNRS – Sorbonne Université, 57 rue Cuvier, CP38, F-75005, Paris, France.